What motivational goals do Argentines seek to satisfy in and out their jobs? Socio-labor study on Argentine values - Genoud, María Andrea (Sociedad y Economía, 2010)
This article describes the results of a research of qualitative nature, which deals with basic Argentine human and labor values within a globalized world context. A better axiological diagnosis of our particular situation will allow fresh thinking on how to create more responsible educational processes in terms of business administration, more committed to the long term, that make easier the articulation of not only profitable, but also sustainable socio-economic developments.